2007
DOI: 10.2319/0003-3219(2007)077[0337:sbscot]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength Comparison of Two Adhesive Systems Following Thermocycling

Abstract: Although SBS and ARI scores were not significantly different for the two adhesives, clinicians need to take into consideration the other properties of the adhesives before using them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
2
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 24 publications
(39 reference statements)
6
67
2
4
Order By: Relevance
“…In addition, it was recently shown that following thermocycling, the SBSs of brackets bonded using an RMGI and a composite resin were not significantly different. 45 The present results also indicated that the brackets bonded using Fuji Ortho LC failed in a different mode than those bonded using the Transbond adhesive system. In general, bond failure for brackets bonded using Fuji Ortho LC with either conditioner occurred at the enamel-adhesive interface, while brackets bonded using Transbond typically failed at the bracket-adhesive interface.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, it was recently shown that following thermocycling, the SBSs of brackets bonded using an RMGI and a composite resin were not significantly different. 45 The present results also indicated that the brackets bonded using Fuji Ortho LC failed in a different mode than those bonded using the Transbond adhesive system. In general, bond failure for brackets bonded using Fuji Ortho LC with either conditioner occurred at the enamel-adhesive interface, while brackets bonded using Transbond typically failed at the bracket-adhesive interface.…”
Section: Discussionsupporting
confidence: 60%
“…This value is similar to published values for the Transbond Plus SEP adhesive system, which have ranged from 6.1 MPa to 10.4 MPa, although these studies used different experimental conditions. 16,17 On the other hand, the mean bond strength obtained with the Fuji Ortho LC Automix in this study was 3.7 MPa, which was lower than previously published values (3.7-12.6 MPa) for other types of RMGIC (Fuji Ortho LC and Photac-Fil Aplicap). Most studies refer to an article by Reynolds (1975), who proposed that 6 to 8 MPa was a clinically acceptable value for the bracket bond strength.…”
Section: Discussioncontrasting
confidence: 54%
“…The SBS values for orthodontic brackets attached to tooth enamel with resin composites or glass ionomer-type adhesives have been reported to be in the range of 4-26 MPa. [14][15][16][17][18][19] The selection of the premolar brackets instead of maxillary central incisor brackets was based upon ready availability of the former. The curvature of the bracket against the flat surface of the PCM probably resulted in SBS values that were lower than those that would have resulted if central incisor brackets with smaller curvature were used as reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Bis-acryl-composite resins, as compared to poly methylmethacrylate or poly ethylmethacrylate, show low exothermic reaction during setting, better strength, adequate margin adaptation, and superior color stability. 10 The range of force required for translatory movement of teeth is reported to be 70-120 g; for extrusion, 35-60 g. 11,12 Comparing such forces, Reynolds 13 has suggested that a minimum tensile bonding strength of [14][15][16][17][18][19] Information related to the bond strength of brackets with various other restorative and experimental materials is also available [20][21][22][23] ; however, information specifically related to PCMs is rather limited. 21 The objective of this in vitro study was to compare the shear bond strength (SBS) between four widely and commonly used PCMs and two different types of orthodontic brackets, using two separate adhesive agents.…”
Section: Introductionmentioning
confidence: 99%